2021
DOI: 10.1111/ner.13327
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Neurostimulation on Poststroke Dysphagia: A Synthesis of Current Evidence From Randomized Controlled Trials

Abstract: Objectives: To evaluate the effects of neurostimulation, including repetitive transcranial magnetic stimulation (rTMS), transcranial direct current stimulation (tDCS) and pharyngeal electrical stimulation (PES), for poststroke dysphagia based on evidence from randomized controlled trials (RCTs).Materials and Methods: Electronic databases were systematically searched between January 1985 and June 2020 and studies were included based on prespecified selection criteria. The quality of studies was evaluated and da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
84
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(88 citation statements)
references
References 70 publications
3
84
1
Order By: Relevance
“…Over the past decade, clinical studies have demonstrated positive effects of NIBS in patients with post-stroke dysphagia [2]. Low-frequency rTMS has been used to suppress cortical excitability of the unaffected hemisphere to reduce interhemispheric inhibition [51-54], while high-frequency rTMS applied to the affected hemisphere was used to increase cortical excitability and overcome interhemispheric imbalance [52,55].…”
Section: Central (Cortical and Cerebellar) Neurostimulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the past decade, clinical studies have demonstrated positive effects of NIBS in patients with post-stroke dysphagia [2]. Low-frequency rTMS has been used to suppress cortical excitability of the unaffected hemisphere to reduce interhemispheric inhibition [51-54], while high-frequency rTMS applied to the affected hemisphere was used to increase cortical excitability and overcome interhemispheric imbalance [52,55].…”
Section: Central (Cortical and Cerebellar) Neurostimulationmentioning
confidence: 99%
“…Research on rehabilitation of swallowing function after brain injury has started to focus on strategies that promote such plasticity. Neurostimulation techniques, including non-invasive brain stimulation (NIBS) and stimulatory approaches that target the afferent neural pathways of swallowing, have been studied vigorously in recent years and the findings are encouraging [2]. However, there is substantial variability in the responsiveness toward these treatments.…”
Section: Introductionmentioning
confidence: 99%
“…ES of oropharyngeal mucosa is an approved therapy for dysphagia following stroke. In theory, ES is thought to drive neuroplasticity by activating sensory bres [37]. For pharyngeal electric stimulation (PES), an electrode mounted on a nasogastric tube is placed into the pharynx with contact to the posterior wall.…”
Section: Discussionmentioning
confidence: 99%
“…ES of oropharyngeal mucosa is an approved therapy for dysphagia following stroke. In theory, ES is thought to drive neuroplasticity by activating sensory fibres 37 . For pharyngeal electric stimulation (PES), an electrode mounted on a nasogastric tube is placed into the pharynx with contact to the posterior wall.…”
Section: Discussionmentioning
confidence: 99%